Smart Subsidies for Catchment Conservation in Malawi - New York University; International Food Policy Research Institute; Lilongwe University of Agriculture and Natural Resources (International Food Policy Research Institute, 2018)
This dataset includes a baseline and endline survey from a cluster-randomized sample of households within villages covering the five uppermost Extension Planning Areas (EPAs) in the Shire River Basin in southern Malawi, spanning the districts of Balaka, Machinga, and Zomba. These EPAs were identified by the Malawian Department of Land Resources Conservation (DLRC) as the key riparian areas to the Shire River. Additionally, it includes registration and monitoring data from two years of the experimental intervention, with the intervention consisting of varying incentive structures and visual monitoring of land management practices. Finally, the data include an accounting of what, if anything, recipients purchased with the voucher they received. In sum, these data include detailed assessments of farm and household characteristics; detailed crop-level measurements of inputs and production for all plots (baseline and endline surveys) or the main plot (intervention registrations; summaries at plot-level for all other plots); assessments of access to services, coupons, and markets; an economic experiment designed to assess marginal willingness-to-accept a conservation agriculture (CA) incentive (baseline), and the perceived risks associated with CA (year 2 intervention and endline).